Identification of metal tolerance proteins (MTP) and their gene expression under drought stress in potato (Solanum tuberosum L.) - Zahra HAJIBARAT; Abbas SAIDI (Acta Agriculturae Slovenica)
Metal tolerance proteins (MTPs) are as metal efflux transporters, existing extensively at all plant sections and play significant roles in regulation of the metal levels in biological processes. In the current study, phylogenetic relationships, gene structures, conserved motifs, and StMTP domains were analyzed. Here, 12 MTP genes in S. tuberosum were detected and categorized in three major clusters namely Fe/Zn-MTP, Zn-MTP, and Mn-MTP and seven groups (1, 5, 6, 7, 8, 9, and 11) according to phylogenetic relationships. Based on in silico and qPCR analysis, all of StMTPs included a cation diffusion facilitator (CDF) domains and the putative Mn-MTP harbored the ZT-dimer. An evolutionary analysis indicated that StMTP genes had undergone gene duplication leading to gene loss and gene expansion events. Analysis of transcription factor binding sites (TFBS) and microRNA in promoter region and coding sequence of StMTP genes revealed the presence of 5312 putative TFBS and 13 StmiRNAs. The analysis of promoter regions of StMTP genes possess various frequencies of TFBS, illustrating various responses in different growth and developmental stages as well as under abiotic stress. Expression profile analysis revealed that the StMTP9 were up-regulated in leaves and stem, while, StMTP8 up-regulated in leaves. Both genes down-regulated in tubers, roots as well as under drought stress. These results will provide a better insight for functional characterization of StMTP genes and can be helpful to elucidate the biological structure of their genes in potato.